In vitro 5-LOX and COX inhibitory activity of isolates from Eleusine indica Linn Gaertner (Poaceae) aerial shoots - Jacinto, Adrien Kyle M.​
Goose grass (Eleusine indica) is a locally abundant weed traditionally used as an herbal medicine. Recent studies supported its use in inflammatory processes as evidence by the reduction of LPS-induced inflammation in vitro and in vivo. The aim of this research was to evaluate anti-inflammatory activity of the isolates from E. indica in the context of 5-LOX and COX inhibition. Drugs able to block the two main arachidonic acid pathways is of pharmacological interest due to wide range of anti-inflammatory activity with no ulcerogenic risk.